An insight on the speciation and genetical imprint of bicarbonate ion in the groundwater along K/T boundary, South India - Devaraj, N.; Chidambaram, S.; Gantayat, R.; Thivya, C.; Thilagavathi, R.; Prasanna, Mohan Viswanathan; Panda, B.; Adithya, V.; Vasudevan, U.; Pradeep, K.; Paramaguru, P.; Ganesh, N. (Springer, 2018)
Groundwater stored in sand, clay, and underground rocks that act as huge aquifers of water have been vastly explored by human civilization for drinking and irrigation purposes. This underlying sand, clay, and rocks greatly influence the chemistry of groundwater by fluctuation in various concentrations of ions. The geochemistry of Ariyalur region was studied by taking 142 samples in both Pre monsoon (PRM) and Post monsoon (POM) seasons. Analysis for crucial cations and anions like K+, Na+, F-, Cl-, HCO3-, Mg2+, Ca2+, SO42-, PO43-, NO3-, and H4SiO4and the physico-chemical variables like pH, total dissolved solid (TDS), and electrical conductivity (EC) were carried out to understand the suitability of groundwater. From all these information, Piper-plot has been used to analyze the water type in both the seasons. The study revealed that in both the seasons, HCO3-covers the major factors followed by H2CO3which are responsible for the change of chemistry of groundwater and proved its importance in the study area. Hence to determine the relationship of HCO3-with other ions, various charts were used. To obtain the origin of this HCO3-and reactions related to it, correlation of different species like HCO3, CaHCO3, MgHCO3, NaHCO3, CaCO3, MgCO3, NaCO3, and H2CO3were analyzed along with major physico-chemical variables like pH and logpCO2. The factor analysis for these species revealed the processes and reactions taking place in the study area. The contour diagrams for all the species in both the season has revealed the origin of HCO3-and dissolution by comparing lithology and geology of the study area.